IMPLEMENTATION OF SOCIO-SCIENTIFIC ISSUES LEARNING MODEL IN ENVIRONMENTAL KNOWLEDGE COURSE IN THE STATE UNIVERSITY OF SURABAYA - Listyoningsih, Elmi; Kirana, Tjandra; Rahayu, Yuni Sri (Universitas Negeri Surabaya, 2014)
To promote connection between biology content and social context, students need to be involved in Socio-scientific Issues (SSI) learning model. In doing so, involving 29 students majoring Biology Education enrolled in Environmental Knowledge course, to observe student’s perception and student’s achievement. Data were collected through questionnaires, test and observation, and then analyzed using qualitative descriptive technique. The findings reported that student’s perception was increased toward SSI learning model (N-Gain=0,4), all of students were successful in student’s achievement based on increasing of student’s achievement (N-Gain=0,4) and there was positive and fair correlation between student’s perception and student’s achievement (rxy=0,4). However, further investigation need to be conducted for examining student’s attitudes towards SSI learning model.